A Comprehensive Review on Documentation Practices in the Pharmaceutical Manufacturing Industry - R., Thanuja; Kumar, K. Vinod; Sree, Byreddy Divya; S., Karthick; Reshma, T (Jordan Journal of Pharmaceutical Sciences, 2024)
This review sheds light on the crucial role of documentation in the pharmaceutical manufacturing industry, a sector where quality control and regulatory compliance are critical. Documentation, from standard operating procedures to validation protocols, underpins quality assurance systems by shaping and improving manufacturing processes. We examine its significance in maintaining product quality, patient safety, and meeting regulatory requirements, particularly in FDA and EMA audits. Additionally, we explore the digital transformation in documentation practices, introducing of electronic batch records, and the associated challenges and opportunities. The paper underscores the necessity for robust, accurate, and timely documentation, emphasizing it as a pledge to product quality, patient safety, and public health.